A new mechanism of direct coupling of laser energy to ions. (17th June 2020) - Vashistha, Ayushi; Mandal, Devshree; Kumar, Atul; Shukla, Chandrasekhar; Das, Amita
Abstract: The well-known schemes (e.g. Brunel mechanism, resonance absorption, J → × B → heating etc) couple laser energy to the lighter electron species of the plasma. In this work, a fundamentally new mechanism of laser energy absorption directly to the heavier ion species has been proposed. The mechanism relies on the difference between the E → × B → drifts of electron and ions in the oscillating electric field of the laser and an external magnetic field to create charge density perturbations. The proposed mechanism is verified with the help of particle-in-cell (PIC) simulations using OSIRIS4.0.